Simple retrograde cerebral perfusion is as good as complex antegrade cerebral perfusion for hemiarch replacement - Tanaka, Akiko; Estrera, Anthony L. (Journal of Visualized Surgery, 2018)
Cerebral complication is a major concern after aortic arch surgery, which may lead to death. Thus, cerebral protection strategy plays the key role to obtain respectable results in aortic arch repair. Deep hypothermic circulatory arrest was introduced in 1970s to decrease the ischemic insults to the brain. However, safe duration of circulatory arrest time was limited to 30 minutes. The 1990s was the decade of evolution for cerebral protection, in which two adjuncts for deep hypothermic circulatory arrest were introduced: retrograde and antegrade cerebral perfusion (ACP) techniques. These two cerebral perfusion techniques significantly decreased incidence of postoperative neurological dysfunction and mortality after aortic arch surgery. Although there are no large prospective studies that demonstrate which perfusion technique provide better outcomes, multiple retrospective studies implicate that ACP may decrease cerebral complications compared to retrograde cerebral perfusion (RCP) when a long circulatory arrest time is required during aortic arch reconstructions. To date, many surgeons favor ACP over RCP during a complex aortic arch repair, such as total arch replacement and hybrid arch replacement. However, the question is whether the use of ACP is necessary during a short, limited circulatory arrest time, such as hemiarch replacement? There is a paucity of data that proves the advantages of a complex ACP over a simple RCP for a short circulatory arrest time. RCP with deep hypothermic circulatory arrest is the simple, efficient cerebral protection technique with minimal interference to the surgical field—and it potentially allows to flush atheromatous debris out from the arch vessels. Thus, it is the preferred adjunct to deep hypothermic circulatory arrest during hemiarch replacement in our institution.